ChemInform Abstract: Practical and Convenient Synthesis of 1, 6‐Di‐ or 1, 2, 5, 6‐Tetra‐arylhexa‐1, 3, 5‐trienes by the Dimerization of Pd(0)‐Complexed Alkenylcarbenes Generated from π‐Allylpalladium Intermediates. Issue 50 (16th December 2014) - Horino, Yoshikazu; Takahashi, Yu; Koketsu, Kaori; Abe, Hitoshi; Tsuge, Kiyoshi
Abstract Application of the 4‐methoxyphenyl‐substituted substrate analogue of (I) yields an instable mixtures of isomers.